The gift - Patterson, James, 1947- (Patterson, James, 1947- Witch & wizard novels., 2011)
After escaping imprisonment by the totalitarian regime known as the New Order, siblings Wisty and Whit Allgood, who possess magical powers, establish themselves as leaders of the Resistance, a hidden community of teenagers like themselves, hunted by the state and determined to defy its ban on the arts, magic, and all other forms of creativity.